1991
DOI: 10.1111/j.1471-4159.1991.tb02591.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Synthetase in Oligodendrocytes and Astrocytes: New Biochemical and Immunocytochemical Evidence

Abstract: The results of recent immunocytochemical experiments suggest that glutamine synthetase (GS) in the rat CNS may not be confined to astrocytes. In the present study, GS activity was assayed in oligodendrocytes isolated from bovine brain and in oligodendrocytes, astrocytes, and neurons isolated from rat forebrain, and the results were compared with new immunochemical data. Among the cells isolated from rat brain, astrocytes had the highest specific activities of GS, followed by oligodendrocytes. Oligodendrocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
1
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(69 citation statements)
references
References 28 publications
6
60
1
2
Order By: Relevance
“…62 High levels of the enzyme glutamine synthetase are found in astrocytes, which in conjunction with a specific glutamate transporter, remove and detoxify extracellular glutamate and provide the neuronal substrate glutamine, as part of the glutamate/glutamine cycle. 64,65 Astrocytes store glycogen and have the potential to provide lactate as an alternative aerobic energy substrate for neurons during recovery, as well as to maintain the osmotic environment. [67][68][69] Astrocytes produce a variety of cytokines and growth factors and function in the CNS as mediators of immune and inflammatory responses that may contribute to both neurotoxic and neuroprotective effects.…”
Section: Discussionmentioning
confidence: 99%
“…62 High levels of the enzyme glutamine synthetase are found in astrocytes, which in conjunction with a specific glutamate transporter, remove and detoxify extracellular glutamate and provide the neuronal substrate glutamine, as part of the glutamate/glutamine cycle. 64,65 Astrocytes store glycogen and have the potential to provide lactate as an alternative aerobic energy substrate for neurons during recovery, as well as to maintain the osmotic environment. [67][68][69] Astrocytes produce a variety of cytokines and growth factors and function in the CNS as mediators of immune and inflammatory responses that may contribute to both neurotoxic and neuroprotective effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, GS immunoreactivity in oligodendrocytes was demonstrated in the rat central nervous system, including the optic tract, in the 1990s [50][51] . GS immunoreactivity in oligodendrocytes was subsequently reported in the optic nerve and optic chiasm.…”
Section: Chemoarchitecture Of the Myelinated (M) Regionmentioning
confidence: 99%
“…This ABHD6 staining may in fact be glial in nature. To test this, we costained with glutamine synthetase, a marker for some astrocytes and oligodendrocytes (Norenberg and Martinez-Hernandez, 1979;Fages et al, 1988;Tansey et al, 1991). However, we found that ABHD6 and glutamine synthetase staining were mutually exclusive (Fig.…”
Section: Mgl Limits Duration Of Dse 1223mentioning
confidence: 99%